Analisis Hasil Mesin Terjemahan dalam Pengajaran Penerjemahan - Aris Wuryantoro (Jurnal Pendidikan, 2011)
In line with the development of technology, translation technic has developed significantly in terms of the utility of translation machine, like that in Google translation. This technique is now being commonly used by people from all education levels. This phenomenon attracts the researcher to identify the quality of the results of translation machine. Translation is basically a process of transfering massage from one language to another, both the meaning and the language corpus. A translator has to cope not only with the source and target language systems but also the discipline in question. This research applies qualitative method studying on verbal materials in the forms of words, phrases, sentences and even paragraphs. The researcher makes use of articles from verious disciplines, like economy, technology, sosial and health as the source of data. The analysis shows that the translation texts resulted from translation machine are significantly defective in carrying out meanings in the level of words, phrases and sentences; which come with the different contexts. In spite of the inappropriateness in translation results, the translation machine is still helpful to some extents.